A educação contextualizada e a formação continuada do Projeto Contexto: trajetórias e relatos dos professores do ensino fundamental em Ipaporanga-CE - Maciel Junior, Wellington de Sousa (2020)
The present study is based on the intention to answer the following central question: What are the contributions of continuing education, based on the reports of teachers who work in the final years of elementary school for the promotion of Contextualized Education in the Semi-arid region of Ceará? The general objective of this study is to understand what are the contributions of the continuing education of the Context Project in the teaching performance, having as specific objectives: to reflect on the conceptions of Contextualized Education in the Brazilian Semiarid Region; discuss the continuing education of teachers developed by the Contexto Project and identify the contributions of continuing education to pedagogical practices through teachers' reports. Researching on the formation of teachers, provokes reflection on the aspects that are integrated in the core of the teaching profession, and when evidencing the Brazilian Semiarid Region, there is a lack of training policies that are linked to the realities of the subjects in the country spaces of the country. This research, which besides being about Contextualized Education, having as basis the reflection and the understanding of the specificities of the Semi-Arid environment, breaking with the old paradigms of a colonizing education, also give emphasis to the continued training carried out by the Context Project for the teachers who work in the final years of elementary school, using as a reference for the epistemological foundation of the discussions: Malvezzi (2007); Baptista and Campos (2014); Arroyo, Caldart, Molina (2004); Silva (2004, 2006); Freire (1979); Saviani (2006); Reis (2009); Souza (2010); Conti and Schroeder (2013); Castro (2015), among others. To answer the central question and the respective objectives, a qualitative approach was chosen to better understand the interpretations of the investigated object. To collect the reports, semi-structured interviews and a focus group were used, while the organization and selection of the data took place through the content analysis method. From the narratives of the research participants, it was concluded that it is during the activities developed through the training provided by the Contexto Project, that the teachers inserted in Rural Education produce knowledge of peasant culture, in order to value this knowledge, giving meaning to the teaching and the daily life of the subjects inserted in the rural spaces and that the formations contribute in the improvement of the pedagogical praxis of the teachers of Ipaporanga - Ceará.